45-(5x+8)=5(x+3)+x

Simple and best practice solution for 45-(5x+8)=5(x+3)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 45-(5x+8)=5(x+3)+x equation:


Simplifying
45 + -1(5x + 8) = 5(x + 3) + x

Reorder the terms:
45 + -1(8 + 5x) = 5(x + 3) + x
45 + (8 * -1 + 5x * -1) = 5(x + 3) + x
45 + (-8 + -5x) = 5(x + 3) + x

Combine like terms: 45 + -8 = 37
37 + -5x = 5(x + 3) + x

Reorder the terms:
37 + -5x = 5(3 + x) + x
37 + -5x = (3 * 5 + x * 5) + x
37 + -5x = (15 + 5x) + x

Combine like terms: 5x + x = 6x
37 + -5x = 15 + 6x

Solving
37 + -5x = 15 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
37 + -5x + -6x = 15 + 6x + -6x

Combine like terms: -5x + -6x = -11x
37 + -11x = 15 + 6x + -6x

Combine like terms: 6x + -6x = 0
37 + -11x = 15 + 0
37 + -11x = 15

Add '-37' to each side of the equation.
37 + -37 + -11x = 15 + -37

Combine like terms: 37 + -37 = 0
0 + -11x = 15 + -37
-11x = 15 + -37

Combine like terms: 15 + -37 = -22
-11x = -22

Divide each side by '-11'.
x = 2

Simplifying
x = 2

See similar equations:

| 1-3(2)=7 | | -(2x-4)=22 | | x-3(2)=7 | | 2x+8x-10=0 | | Ln(x)=0.21 | | lnx=0.21 | | 17y-7=9+2y | | 6x^2+5x+24=0 | | 7z-3=8z-9 | | 4x-20x=11 | | 4=5(x-2) | | 1/3*x^3*y^3=9 | | x^3+4x^2+8x+2=0 | | x^3-4x^2+8x+2=0 | | x^3-4x^2-8x-1=0 | | x^3-4x^2-8x+2=0 | | 4x^2-25x+20=-6x+8 | | b-5/3=2 | | 0=5b-30 | | 10(s-5)=-99 | | 0=56-30 | | z-6/9=7 | | x-8/9=2 | | f(-x)=7x+5 | | 60=2l+2(5w) | | 2(2+3y)-6y=4 | | 5(4+0.5w)+7w=1 | | =-3y^2+2y | | 81=16r^4 | | S+-4=7.3 | | (3x-y)/3 | | 4.2x-86=2.7x+7 |

Equations solver categories